FORMATION OF THE PROFESSIONAL COMPETENCE OF POLYGRAPH EXAMINERS IN THE SECURITY AND DEFENSE SECTOR OF UKRAINE IN ACCORDANCE WITH INTERNATIONAL STANDARDS OF PRACTICE - Snihur, Lyudmyla; Zdebskyi, Dmytro (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2025)
B a c k g r o u n d . This article addresses the development of professional competence of polygraph examiners in Ukraine's security and defense sector in accordance with international practice standards. The process of polygraph examiner training is examined, with emphasis on the importance of applying valid polygraph research methodologies and quality control as key factors of professionalization, along with the integration of international experience to improve the accuracy and effectiveness of polygraph examinations.M e t h o d s . The study employed a comprehensive set of methods, including theoretical analysis of regulatory legal acts and scientific sources; the concrete-historical method to investigate the dynamics of polygraph examiner training; generalization of foreign experience, particularly the practices of the American Polygraph Association; and empirical approaches to assess professional competence in accordance with international standards.R e s u l t s . Based on the research, a model for developing the professional competence of polygraph examiners was formulated, grounded in international standards (ASTM, APA), the national classifier of professions (Amendment No. 10 to DK 003:2010), the Dreyfus model, and Albert Bandura's self-efficacy theory. Five competence levels were identified: novice, beginner, competent, experienced, and expert, each characterized by criteria such as education, experience, number of field examinations, self-efficacy, and professional autonomy. The proposed tables enable a qualitative assessment of professional development and planning for qualification improvement.C o n c l u s i o n s . The professional competence of polygraph examiners is crucial for the effectiveness of Ukraine's security sector. Its formation is based on theoretical and practical training, professional experience, adherence to valid methodologies, and quality control. The proposed competency model by levels (from novice to expert) adapts the Dreyfus model and international standards (ASTM, APA). It enables the standardization of certification, professional development, and qualification enhancement. The establishment of a National Polygraph School will ensure systematic training and quality of polygraph examinations under conditions of military threats.
Keywords: professional competence, competence formation, polygraph examiner training, international practice standards, National Polygraph School